HUBUNGAN FAKTOR LINGKUNGAN FISIK DAN PERILAKU PENGHUNI RUMAH DENGAN KEJADIAN PENYAKIT MALARIA DI WILAYAH KERJA PUSKESMAS KOKAP II, KABUPATEN KULON PROGO, DAERAH ISTIMEWA YOGYAKARTA - Noviarti, Pratiwi Ika; Joko, Tri; Dewanti, Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Malaria is still one of public health problems that is responsible for the high number of death in many countries all over the world until nowadays. It is a disease that threatens people, especially those who live in endemic area. High morbidity and other issues that arise as a result of malaria can impede the development in health field. In Kulon Progo Regency, the API (Annual Parasite Incidence) was 0,28 0/00 in 2013, 0,20 0/00 in 2014, and until February 2015, it has been 29 cases with API 0,07 0/00. Some factors that influence malaria disease outbreak are physical environment and residents’ behavior. This research aims to analyze the relation between physical environment and residents’ behavior with malaria diseases outbreak in Puskesmas Kokap II working area. Observational analysis method was employed to do the research, with case control approach. The samples of the research were Malaria sufferers in January 2012 up to February 2015 in Puskesmas Kokap II working area, Kulon Progo Regency. There were 37 respondents in case group and also 37 respondents in control group. The data analysis used chi square test and odds ratio (OR). The result of the research showed that there were relations between the presence of ceilings (p value = 0,000 OR = 22,969), the types of the wall (p value = 0,000 OR = 8,488), the presence of breeding places, the presence of resting places (p value = 0,000 OR = 58,556), outdoor activities (p value = 0,000 OR = 10,828), the use of long clothes (p value = 0,000 OR = 16,074), the use of mosquito nets (p value = 0,007 OR = 5,022), and cleaning activities (p value = 0,001 OR = 5,317) with Malaria disease outbreak. However, the temperature inside the house, the humidity inside the house, the lighting intensity inside the house, the presence of wire gauzes, the presence of cages, and the use of drugs, had no relation with Malaria disease.The conclusion of the research is the presence of ceilings, the types of wall, the presence of breeding places, the presence of resting places, outdoor activities, the use of long clothes, the use of mosquito nets, and cleaning activities had relation with Malaria disease outbreak.